Hazardous materials labels - Smith, Bo; Luttrell, Steve (United State : Marcom)
This program help employees understand the characteristics of different labeling systems and the ways that each convey information. By recognizing the differences and similarities of these systems, employees will be better prepared to work safely around hazardous materials. One important method for identifying hazardous materials is through the use of container labels
Content on videodisk: Department of Transportation (DOT) hazard class labels - United Nation (UN) Identification Numbers -Hazardous Material Identification System (HMIS)-National Fire Prevention Association (NFPA) labels - Hazardous waste labels
DVD training program
Executive producer, Donald Leonard ; editor,Joseph Pukatsch
DVD format
Keywords: Labels; Chemicals -- Safety measures